Further evidence on the role of heparan sulfate as protamine acceptor during the decondensation of human spermatozoa - Romanato, M. (2005)
Background: Human spermatozoa decondense in vitro upon exposure to heparin and glutathione. Glutathione is also the disulfide bond reducer in vivo, and heparan sulfate, a functional analogue of heparin, has been proposed as the protamine acceptor. The aim of this study was to evaluate the decondensing ability of chemically modified heparins and different glycosaminoglycans (GAGs) on isolated sperm nuclei in vitro, and to analyse the possible role of different GAGs as protamine acceptors. Methods: Capacitated spermatozoa and isolated sperm nuclei from normospermic semen samples were decondensed in the presence of heparin (or its equivalent) and glutathione. After fixation with glutaraldehyde, the percentage of decondensed spermatozoa and nuclei was determined under phase-contrast. Proteins were extracted from sperm nuclei previously incubated in the presence of gluhathione and different GAGs by incubation with urea-β-meracptoethanol-NaCl, and analysed by acid polyacrylamide gel electrophoresis. Results: The ability of desulfated heparins and other GAGs to decondense isolated nuclei mirrored exactly the decondensation of capacitated spermatozoa, the only difference being the level of maximum decondensation achieved. Heparan sulfate and heparin, but not other GAGs, were able to release protamines from sperm chromatin. Conclusions: Heparan sulfate could be functioning as protamine acceptor in vivo during human sperm nuclear decondensation. © The Author 2005. Published by Oxford University Press on behalf of the European Society of Human Reproduction and Embryology. All rights reserved.